Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward and Peppard pada Fakultas Bisnis Universitas Universal - Antonio Pangestu, Amora; Efanly, Efanly; Rio, Firstan (Fakultas Komputer - Universitas Universal, 2022)
The Faculty of Business is a field of study that studies financial management, marketing, bookkeeping, and matters regarding sustainability related to business in the business world, and the Faculty of Business is also popular because of its broad and relevant job prospects to the economy. The Faculty of Business is one of the faculties at Universal University which has the vision to excel in the sustainable field. But the problems faced in taking market share are currently not too broad and competition in getting students to enroll at the Universal University Faculty of Business and the application of Information Systems is not good enough to support learning at the Computer Faculty. Therefore there is a need for proper IS/IT strategic planning using the Ward and Peppard method, and analysis using SWOT, Five Forces Porter, Value Chain, and McFarlan Strategy Grid.